Bilateral Giant Pulmonary Emphysematous Bullae in a Calf - Ocarino, Natália M.; Paniago, Juliana G.; Lasmar, Pedro V. F.; Carvalho, Antônio U.; Facury Filho, Elias J.; Serakides, Rogeria (Brazilian Journal of Veterinary Pathology, 2011)
Bilateral giant pulmonary emphysematous bullae were diagnosed in a calf. The necropsy revealed two gas-filled bullae completely involving the right and left diaphragmatic pulmonary lobes. Histologically, the outer surface of the giant bullae was made of visceral pleura while the inner layer consisted of the adjacent lung, which presented signs of atelectasis or emphysema. Aspiration bronchopneumonia was observed in the right and left apical lobes. The animal died as the result of acute respiratory failure.